The depiction of sexism experienced by female character Elizabeth Zott in Lessons in Chemistry (2023) Series - Mirani, Indar; Elve Oktaviani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
This study employs the sexism theory developed by Peter Glick and Susan Fiske to examine the portrayal of sexism in the 1950s through the character of Elizabeth Zott in the series Lessons in Chemistry (2023). The research method is qualitative with a descriptive approach. This research shows that Elizabeth Zott encounters two forms of sexism in a male-dominated workplace: hostile sexism, which includes direct hostility and discrimination, and benevolent sexism, which is more subtle and paternalistic but still excludes women from equal opportunities. Elizabeth is a woman who boldly rejects the traditional roles expected by a patriarchal society and confidently asserts her independence as an individual, despite social pressures. In the face of hostile sexism, Elizabeth is determined and courageous, continuing her career in science despite facing direct discrimination and challenges. She also challenges social expectations that limit women's roles and demands change for gender equality in the face of benevolent sexism. This study highlights Elizabeth's resistance strategies against both forms of sexism and the importance of understanding and addressing various forms of sexism in a male-dominated workplace.